Edukasi Keuangan untuk Generasi Z dalam Merancang Masa Depan Tanpa Utang - Sri Maria Ulfha; Ranggi Radiyanti; Wendy Muliadi; Yenni Yunianingsih; Nita Laila Asyifa; Moch Alfiansyah (BADAN PENERBIT STIEPARI PRESS, 2025)
This Community Service Program (PKM) aims to provide financial education to early-semester university students at a private institution in Subang. Participants, aged 18–22 and part of Generation Z, are often exposed to consumerist lifestyles and social pressure driven by digital media. The program delivered basic knowledge on financial planning, the risks of online loans (pinjol), and the dangers of impulsive use of pay later services. The educational session was conducted through interactive socialization, guided by lecturers specializing in financial management. A real-life case study was also presented, illustrating how a student became trapped in a cycle of debt due to a lack of financial literacy. The participants showed high enthusiasm, actively engaging in discussions and Q&A sessions. This activity is expected to be an initial step in raising financial awareness among students so they can manage their spending wisely and avoid falling into consumer debt traps.